Kajian Pustaka: Bakteri Asam Laktat Halotoleran: Prospek Pengembangan Metoda Baru Untuk Menekan Pembentukan Histamin pada Hasil Laut - Ramona, Yan; Andriani, Luh Nyoman Ary Metta; Sukmaningsih, Anak Agung Sagung Alit (Bumi Lestari, 2024)
Abstract Histamine is an amine biogenic compound, frequently reported to cause poisoning among people who consume fishes with high level of histamine. Such compound is produced by histamine producing bacteria (HPB) belong to family of Enterobacteriaceae. Histidine decarboxylase produced by HPB plays a central role to convert free histidine in the fish meat into histamine, resulting in accumulation of histamine in the fish meat. Many efforts, including low temperature storage, ozone, and brine treatment) have been applied to cope with/prevent histamine accumulation in seafood products. However, those methods have some disadvantages, such as costly or have potential to change texture or structure of the products being preserved. In this review therefore, some aspects (including application of lactic acid bacteria (LAB) to control histamine production, characteristics of LAB required, tolerance of LAB to high level of salt, and the role of LAB to suppress HPB growth, and suppression of histamine production) are comprehensively reviewed. All information was extracted from related scientific articles published in the last decade. Keywords: Allergy ; Biogenic agent ; Histidine decarboxylase ; Lactic acid bacteria ; Tuna